Odgovorno upravljanje virov v javnem sektorju - Brezavšček, Andrej (Javna uprava, 2023)
The article examines two cases of resource management within the public sector, highlighting differences in their efficiency and societal benefits. The first case pertains to the decision of the Health Insurance Institute of Slovenia, which confirms the status of an insured person in mandatory long-term care insurance as of the date of the law’s enactment. The author, a lawyer, questions the rationale behind such decisions, as arguing that insured status directly stems from the law, rendering additional administrative confirmation redundant. The second case focuses on the environmental inspection’s oversight concerning the fulfilment of obligations under the extended producer responsibility scheme. This system pursues the public interest, with producers assuming responsibility for their products beyond their life cycle, thus contributing to recycling and mitigating environment harm. Critiquing the first case for its superfluous administrative burden, which fails to advance public interest, the author underscores the imperative of judicious resource utilisation in the public sector. Conversely, the extended producer responsibility scheme exemplifies how public sector initiatives can effectively bolster public interest, while encouraging producers to manage waste responsibly.
Keywords: javni interes; javni sektor; Slovenija; upravno pravo